Sea monsters - Karst, Ken (Karst, Ken. Enduring mysteries., 2019)
Explores the concept of sea monsters and stories from throughout history of monstrous creature encounters at sea, discussing whether some may be real and real life sources for others, such as giant squids and whales. Includes a glossary.